Anaerobic digestion of cattle manure with palm oil mill effluent as inoculum for biogas production - Muhamad Nasir, Ismail (2011)
Recently, environmental concerns associated with manure waste management generated from the feedlot farming with abattoir integration in Malaysia needs to be carefully addressed. Biogas production from anaerobic digestion of cattle manure is regarded as an alternative, due to the simultaneous benefits of environmental pollution control and meeting the national energy demands. Although anaerobic digestion is a common process for treatment of cattle manure, the digestion rate remains very low. This is due to the low growth rate of the micro-organisms and the presence of hard biodegradable components. Hence, supporting the growth rate of the micro-organisms by the utilization of inoculum can be used as an alternative. One such inoculum is palm oil mill effluent (POME), characterized by having a high nutrient content, mainly oil and fatty acids, and it is also a source of bacteria. In this study, the anaerobic treatment using a 10 L laboratory-scale bioreactor was used to improve the biogas production at different POME mixing ratio, which was performed at 53oC and agitated at 150 rpm. Parameters used for monitoring were the volatile and total solids (VS and TS), temperature, pH, chemical oxygen demand (COD), ammonia nitrogen (NH3-N), biogas production and its respective methane content (%CH4) during the treatment. The research was conducted in batch and semicontinuous modes. The effect of cattle manure with POME inoculum digestion on the biogas potential was investigated at mixing ratio of 5:0, 5:0.5, 5:1 and 5:1.5 and the performance of anaerobic digestion with controlled and uncontrolled pH at various mixing ratios was also studied. Results indicated that stable digestion and high biogas production were achieved at mixing ratio of 5:1.5. The result represents nearly a threefold increase in the biogas production as compared to the digestion of cattle manure alone. The biogas yield and methane content varied from 0.093 to 0.346 m3 kg-1 VS added and 19 to 55% respectively, with a reduction of VS between 22 and 51%. In addition, the final NH3-N concentration ranged from 970 to 1140 mg/L with an average COD removal of 25%. The improvement of cattle manure digestion was attributed to the enhancement of the process by the POME inoculum. Significantly, higher average biogas production and removal rates of VS, TS, COD and NH3-N concentration at controlled pH to that at uncontrolled pH were observed. The average removal at uncontrolled pH could be improved by 1 to 2 times by controlled pH. The results from this study indicated that the improvement of anaerobic digestion of cattle manure with POME as inoculum by controlled pH is feasible.